THE IMPORTANCE OF THE BIOGRAPHICAL METHOD IN REVEALING THE ROOTS OF THE WORK OF ART - Adizova Obodon Istamovna; Karimova Dilafruz Halimovna (International Engineering Journal For Research & Development, 2020)
The given article reveals the expression of the writer’s personal aspects by means of biographical method. It also discusses the writers’ skill of using the biographical method and by this method justifies the existence of the information related to the writer’s biography in literary works